Mitigation of Crop-Raiding Wild Boars in Selected Counties in Sweden: Assessing Feasibility of Electric Fences and Supplementary Feeding - Muchoka, Cecilia M. (University of Embu, 2022)
Wild boar (Sus scrofa) is a wild Suidae native in Europe, North West Africa and Asia. The population of wild boar has drastically increased during the last threedecades in Southern and Central Sweden. This increase in population density has caused severe damages to agricultural fields thus affecting the agricultural economy.There has been a significant loss of wheat, worth over 60 - 70 million Euros between1990 - 2016 due to crop damage by wild boar. This study sought to investigate the effectiveness of electric fencing and supplementary feeding as mitigation measures to crop-raiding of wheat fields by wild boar in South-Central Sweden. The study was carried out in five study sites in Sweden; Koberg, Boo, Bornsjön, Mörkö, and Grimsö. To achieveobjectives one and two, a total of eleven adult wild boar were marked with GPS/GSM-collars in 4 study sites (Koberg, Boo, Mörkö, and Grimsö), and monitoring of crop and habitat selection was performed using GPS units. Data fromthe marked animals was logged in every one hour and then transmitted through the GSM network every seventh hour by SMS to a computer server. Further, a total of 131 feeding stations were used to determine the effectiveness of supplementary food.Objective three, had Boo, Bornsjön, and Mörkö sites experimental wheat fields, i.e., 12 fields with electric fences, and 12 without fences. The fences were constructed by wooden poles in all corners of the field and with small plastic poles in between, and ringed with three metal wires at 20cm, 40cm, and 60 cm high from the ground and supplied with a 12-volt battery. GLMM models in R software (version 3.6.2) and Q GIS (version 3.10.2) were used for the data analysis. Results indicated that wild boar had a high preference for clear-cuts, agricultural fields, anddeciduous forests. The marked animals showed a high preference for crop fields withoat, spring wheat, and mixed crops. A binary logistic model revealed a significant influence of distance to feeding stations on the selection of different habitats and crop fields with both positive and negative effects. Generally, feeding stations influenced the selection of different habitats and crops negatively i.e., the closer a habitat or crop field is to a feeding station, the higher the likelihood of its selection. Besides, distance to main roads significantly influenced the selection of habitats and crop fields with both positive and negative effects. The paired t-test analysis was conducted in R-studio to compare mean harvest yield, pre-harvest damage (< 1 month) and, growing season damage (from sowing period to < 1-month pre-harvest)between electrically fenced fields and unfenced fields. Significant differences in thepre-harvest damaged area were found between the electric fenced and unfenced wheat fields in two of the three study sites. Further, there was an inverse relation between damage size and mean yield in the fenced fields. The gross margin results found that supplementary feeding was effective in preventing wild boar from farmlands. In conclusion, distance to feeding station and main road influenced wild boar selection of different habitat and crop fields differently. Also, the electric fences installed were effective in reducing wild boar damages on the wheat fields. The study recommends farmers and landowners to use electric fences as a way of reducing wild boar damages to their agricultural fields.